Acid Resistance of Concrete Containing Laterite Aggregate as Partial Coarse Aggregate Replacement - Khairunisa, Muthusamy; Vesuvapateran, Gopi; Norul Wahida, Kamaruzaman (Maxwell Scientific Organization, 2014)
In Malaysia, issues of granite aggregate depletion in future due to increasing use in concrete industry and the availability of laterite aggregate locally has initiated studies on concrete produced using laterite aggregate as partial coarse aggregate replacement. Although, replacement of laterite aggregate up to 30% able to produce concrete with the targeted strength but durability of this concrete towards acid attack yet to be investigated. Thus, this study presents and discusses the performance of concrete consisting various percentage of laterite aggregate integrated as partial coarse aggregate replacement upon exposure to acidic environment. Mixes consisting various content of laterite aggregate as partial coarse aggregate replacement ranging from 0, 10, 20, 30, 40 and 50%, respectively were prepared in form of cubes and then subjected to water curing for 28 days before immersed in hydrochloric acid solution for 1800 h. Performance of the specimens were observed through mass loss and strength reduction. Generally, durability performance of concrete produced using up to 20% of laterite aggregate is comparable to plain concrete.